Evaluation of childhood nutrition by dietary survey and stable isotope analyses of hair and breath. Issue 3 (1st February 2018) - Valenzuela, Luciano O.; O'Grady, Shannon P.; Enright, Lindsey E.; Murtaugh, Maureen; Sweeney, Carol; Ehleringer, James R.
Abstract: Objectives: The natural abundances of carbon, nitrogen, and sulfur stable isotopes in hair, and of carbon isotopes in breath serve as quantitative biomarkers of protein and carbohydrate sources, but applicability of isotopes for evaluating children's diet has not been demonstrated. In this study, we sought to describe the stable isotope patterns observed in the hair and breath of children and to assess dietary variations in relation to age and ethnicity, hypothesizing that these would reflect dietary differences across age and ethnic groups and would correlate with intake variables derived from a Food Frequency Questionnaire. Methods: Data were obtained from a cross‐sectional study of non‐Hispanic white ( N = 115) and Hispanic ( N = 97) children, aged 9–16 years, in Salt Lake City, Utah. Sampling included a hair sample, breath samples (AM and PM), and a youth/adolescent food questionnaire (YAQ). Hair was analyzed for carbon (δ 13 C), nitrogen (δ 15 N), and sulfur (δ 34 S) isotopes, and breath samples for δ 13 CAM/PM of respired CO2 . Results: Non‐Hispanic whites had lower δ 13 C, δ 15 N, δ 13 CAM, and δ 13 CPM values than Hispanics. Hair δ 13 C and δ 15 N values were correlated with protein sources, particularly for non‐Hispanics. Breath δ 13 C values were correlated with carbohydrate sources, particularly for Hispanic students. Non‐Hispanic white students reported greater intake of total protein, animal protein, dairy, and grain than Hispanic students. Hispanic students reported higher intake of carbohydrates, particularly sweetened beverages. Conclusion: While YAQ and stable isotope data reflected strong cultural influences in diet, no significant gender‐based nor age‐based differences were detected. Significant covariation between YAQ and isotopes existed and demonstrate the potential of stable isotopes for characterizing children's diet.